Interpersonal Dynamics in Chronic Pain: The Importance of Partner Behaviors and Interactions in Pain Management - Haneen Akram; Farheen Anjum; Alishba Aslam; Sadia Sohail; Omar Zeb Khan; Hina Asghar (Research Journal of Psychology, 2025)
Chronic pain is a complex condition influenced by biological, psychological, and social factors, with interpersonal dynamics playing a crucial role in pain management. This quantitative study examines the impact of partner behaviors and interactions on pain perception and coping strategies in individuals with chronic pain. A sample of 100 participants with diagnosed chronic pain conditions completed validated questionnaires assessing partner support, pain intensity, emotional well-being, and coping mechanisms. The selected sample was the registered patient in hospitals of Lahore. Statistical analyses revealed that supportive partner behaviors, such as empathy and active problem-solving, were significantly associated with lower pain intensity and improved psychological resilience. Conversely, negative partner responses, including invalidation and excessive solicitousness, correlated with increased pain severity and emotional distress. These findings highlight the importance of partner involvement in chronic pain management and suggest that interventions targeting interpersonal dynamics may enhance treatment outcomes.